Prevalência de equinos quarto de milha portadores das mutações causadoras da miopatia por acúmulo de polissacarídeo tipo 1, paralisia periódica hipercalêmica e hipertermia maligna no Brasil - Delfiol, Diego José Zanzarini [UNESP] (2014)
Type 1 polysaccharide storage myopathy (PSSM1), hyperkalemic periodic paralysis (HYPP) and malignant hyperthermia (MH) are considered major genetic diseases identified in Quarter Horses (QH). In Brazil, the molecular test for PSSM1 and MH is not available and the prevalence of both diseases is not known. Regarding HYPP, information about the disease prevalence is limited, although a molecular test is available in the country. The aim of this study was to standardize a molecular test for PSSM1, HYPP and MH, as well as to evaluate the diseases’ prevalence in Brazilian QM. Blood DNA from 741 horses were used and genetic tests for the three diseases were standardized. Samples were sequenced to identify the mutation on GYS1 gene, responsible for the PSSM; on SCN4A gene, responsible for HYPP; and on RYR1 gene, responsible for MH. The prevalence obtained was 6.7% for PSSM1, 4.2% for HYPP and no positive results were found for MH. The results indicate the importance of PSSM1 and HYPP in QM in Brazil. Tests standardization would be useful for the diagnosis of PSSM1 and MH. The identification of positive animals for PSSM1, HYPP and MH would assist on the mating selections and thus reduce the occurrence of these diseases